2021
DOI: 10.1177/03331024211034509
|View full text |Cite
|
Sign up to set email alerts
|

Are PROMs passing the message? A reflection with real-life migraine patients

Abstract: Background Several patient-reported outcome measures are available to monitor headache impact, but are those reliable in real-life clinical practice? Methods Two identical patient-reported outcome measures (HALT-90 and MIDAS) were applied simultaneously in each clinical visit to a series of patients treated with monoclonal antibodies for migraine and intra-individual agreement was evaluated using the intraclass correlation coefficients. Results Our sample included 92 patients, 92.4% females, 45 years old on av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…intra-personal variation in reliability, persisting in repeated applications, decrease motivation to respond etc.) [ 47 ], we cannot exclude that in the future, a more complex scores, encompassing the overall migraine experience, could be proposed. However, herein we have observed a notable reduction in both the number of mean monthly days with painkillers intake and total painkillers intake after the third and sixth galcanezumab administration compared with baseline.…”
Section: Discussionmentioning
confidence: 99%
“…intra-personal variation in reliability, persisting in repeated applications, decrease motivation to respond etc.) [ 47 ], we cannot exclude that in the future, a more complex scores, encompassing the overall migraine experience, could be proposed. However, herein we have observed a notable reduction in both the number of mean monthly days with painkillers intake and total painkillers intake after the third and sixth galcanezumab administration compared with baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring patients with PROMS is less reliable than expected and selecting the ideal set of short and non-intrusive tests to provide useful information is very difficult. Gil-Gouveia et al showed that patients in a PROM assessment can give different answers to the same question asked minutes apart [ 50 ]. This is most likely related to various factors such as interpretive difficulties, educational status, long-term motivation and secondary benefits (e.g., access to reimbursable treatment) but also concentration abilities and current pain status [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…As healthcare professionals strive to enhance patient care, evaluating the effectiveness of these measures in practical day-to-day clinical settings becomes essential. Ensuring the reliability of these measures is crucial for their meaningful integration into the healthcare [77]. The development of new PROMs should focus more on capturing patient perspectives, and direct input from patients is necessary in creating these measures.…”
Section: Patient-reported Outcome Measures Current Challenges and Opp...mentioning
confidence: 99%